Analisis Ergonomi Pada Bahaya Postur Pekerja PLN ULPLTD Labuhan-Sumbawa Berdasarkan SNI 9011:2021 - Hudaningsih, Nurul; Putri, Desi Rohmandani; Dekantari, Rezkia Putri (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
PT. PLN UPLTD Labuhan-Sumbawa as one of the electricity provider units certainly has the potential for danger to workers, one of which is in the Maintenance section. Based on the results of the GOTRAK survey, it was found that all workers had experienced pain or discomfort with a moderate risk level of 44%. The risk level of body pain is in the upper back, lower back, and right shoulder areas, so an ergonomic analysis is needed on the activities of maintenance workers based on SNI 9011:2021. The results of the analysis show that the partition installation worker is in the moderate hazard category with a total score of 6; the pipe installation worker is in the moderate hazard category with a total score of 4; and the Central B cleaning worker is in the hazard category with a total score of 2. Recommendations for improvement are needed by providing proposals for improving work stations including redesigning work stations, adjusting layouts, using personal protective equipment, and improving lighting in the workplace.